Dissolution rates distilled water 20C.xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
performance of dripping tests on IHE residues to measure how the compounds inside the formulation dissolve over time in distilled water at 20C.
Keywords: 'dripping test'; 'IHE residues'